A methodological approach to estimate the overall heat transfer coefficient in olive paste malaxers. (April 2023) - Corti, Ferdinando; Zanoni, Bruno; Parenti, Alessandro; Masella, Piernicola; Breschi, Carlotta; Angeloni, Giulia; Spadi, Agnese; Guerrini, Lorenzo
Abstract: In the olive oil industry, leading-edge technology aims to improve the quality profile of extra virgin olive oil through rigorous control of operative conditions. While effective control of time-temperature conditions appears to be particularly important during malaxation, the low ratio between the heat transfer surface area and the olive paste volume (A/V) is problematic, as is the viscosity of olive paste. These factors may result in a failure to reach the desired processing temperature, especially for short malaxation times. Here, we propose a methodological approach to estimate the overall heat transfer coefficient ( U ), and present the results of tests with four types of malaxers, based on heat exchange models under transient and steady state conditions (TSC and SSC models, respectively). We demonstrate similar performance for both models in estimating U values in the tested olive paste malaxers. The combined application of the above models is shown to be a suitable way to control heat transfer performance. The critical role of the U value is shown with respect to the time needed to reach the desired malaxation temperature, and we suggest that higher A/V values may be incorporated into the design of malaxers. Highlights: Transient and steady state conditions models are equally effective in estimating U . U value can be estimated on industrial scale using a simple approach. Different U values were estimated on laboratory and industrial malaxers.